Popüler Kültürün Sanat Ve Tasarım Ürünlerini Kitschleştirmesi - Kahraman, Mehmet Emin (The Turkish Online Journal of Design Art and Communication, 2015)
In this study, the concept of kitsch as an symbol of popular culture is analyzed. Moreover, its impact on designer’s products is explored in relation to culture as well the use of works of art as kitsch. The use of kitsch, understood as ‘degenerate appreciation’ and ‘fake aesthetics’, in the commercials of some well-known companies constitutes the main problem of this study. The sub-problems of the study are the artists, the subjects and objects of art themselves, becoming kitsch, advertising making use of kitsch and the effect of advertisements in advertising ethics. In order to find answers to these problems, five advertisements/commercials below are analyzed: · The pen “Da Vinci Code” of Tibaldi · The medication Zeldox produced by Pfizer for schizophrenia · The duct tape adverstisement of Teba · Citroen’s Picasso line of cars · The “81 Forests in 81 Cities” commercial of İşbank Common points between the reasons why kitsch objects were preferred for these commercials/advertisements and the products themselves are analyzed. The advertising strategies that make use of kitsch in these commercials with the aim of getting the products bought by large numbers of people are explored. Some recommendations are also made with the ethical dimensions in mind.
Keywords: Sanat; Tasarım; Reklam; Kitsch; Tüketim; Art; Design; Advertisement; Consumption